A coenzyme NAD(P)H hydrogenation regeneration catalyst, and its preparation and application

By regulating the composition of MOF and metal nanoparticles in the MOF-based supported metal nanoparticle catalyst, selective adsorption of carbonyl groups in NAD(P)+ is solved, the problem of low selectivity for coenzyme hydrogenation and regeneration is improved, the catalytic efficiency and selectivity are improved, and it is suitable for large-scale industrial production.

CN117816244BActive Publication Date: 2025-04-22ZHEJIANG NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311537776.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-17
Publication Date
2025-04-22
Estimated Expiration
2043-11-17

AI Technical Summary

Technical Problem

In the prior art, the selectivity of coenzyme NAD(P)+ hydrogenation regeneration 1,4-NAD(P)H is low, which limits the large-scale application of enzyme reduction reactions.

Method used

Using MOF-based supported metal nanoparticle catalyst, selective adsorption of carbonyl groups in NAD(P)+ is achieved by regulating the type of MOF and the loading of metal nanoparticles, thereby improving the hydrogenation selectivity of NAD(P)H.

Benefits of technology

It improves the selectivity and catalytic efficiency of NAD(P)H, solves the problem of low selectivity of coenzyme hydrogenation and regeneration, and provides a new type of coenzyme hydrogenation and regeneration catalyst suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117816244B_ABST
    Figure CN117816244B_ABST
Patent Text Reader

Abstract

The present invention relates to a coenzyme (nicotinamide adenine dinucleotide NADH or its phosphorylated form NADPH) hydrogenation regeneration catalyst, its preparation and application. The carrier of the catalyst is a Ti-based metal-organic framework (MOF), and at least one metal nanoparticle is loaded on the carrier. The metal nanoparticle is at least one of Pt, Pd, Rh, Ir, Ru and / or Ni, and the loading amount of the metal nanoparticle is 0.1-10wt%. The catalyst of the present invention is in the coenzyme NAD (P) + They have shown good catalytic performance in hydrogenation regeneration reactions and have higher 1,4‑NAD(P)H regeneration selectivity than the currently reported hydrogenation regeneration catalysts, and have broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the preparation and application of supported metal nanocatalysts, and specifically relates to a method for coenzyme (NAD + , NADP + ) is a MOF-based metal nanoparticle catalyst for efficient hydrogenation to 1,4-NAD(P)H with enzymatic activity, and its preparation and application. Background Art

[0002] Biocatalysis uses enzymes as catalysts, which have the characteristics of high efficiency and product specificity, and are widely used in the synthesis of chiral drugs and their intermediates. Oxidoreductases are one of the most widely used enzymes and are of great significance in the reduction of C=O double bonds, C=C double bonds, etc. However, most enzyme reduction processes require an equimolar amount of reduced coenzyme nicotinamide adenine dinucleotide (NADH) or its phosphorylated form (NADPH) as a hydrogen source. The coenzyme is expensive, which seriously restricts the large-scale application of enzyme reduction reactions. Therefore, it is urgent to develop NAD(P) + Reduction and regeneration technology lays the foundation for the large-scale application of green enzyme catalytic reduction.

[0003] At present, a variety of coenzyme NAD(P)H regeneration methods have been developed, mainly including stoichiometric method, biocatalytic method, photo / electrocatalytic method, and catalytic hydrogenation method. Among them, the multiphase hydrogenation method using H2 as the hydrogen source has significant advantages over other methods, such as being clean, green, and able to be applied on a large scale, and has attracted more and more attention from researchers. The hydrogenation catalysts for regenerating the coenzyme NAD(P)H using the multiphase hydrogenation regeneration method are mainly supported metal nanoparticle catalysts, including Pt / Al2O3, Pt / SiO2, Pt / TiO2, etc. Studies have shown that the unique adsorption mode of the amide carbonyl and the active center has a great influence on the NAD(P) + The selectivity of the hydrogenation reaction plays a crucial role in precisely regulating NAD(P) + The adsorption pattern on the metal active sites may be a key factor in improving the selectivity of NAD(P)H hydrogenation regeneration.

[0004] Metal-organic framework (MOF) is a kind of highly ordered, highly structurally stable porous framework crystal. Due to the flexibility of the metal nodes, geometry, size and functional groups that form MOF, MOF has the advantages of designability, diversity, and structural tailorability, showing unique advantages and broad application prospects in the field of catalysis (Chemical Society Reviews, 2021, Vol. 50, pp. 5366-5396; Chemical Reviews, 2021, Vol. 121, pp. 12278-12326; Chemical Reviews, 2023, Vol. 123, pp. 5347–5420). Precisely adjustable metal nodes and pore sizes can effectively introduce different adsorption sites near metal nanoparticles, thereby changing the adsorption mode of reactants on the catalyst. For example, by regulating the type of MOF metal nodes, introducing oxophilic metal nodes near metal nanoparticles to selectively adsorb carbonyl groups, and obtaining carbonyl hydrogenation products with high selectivity in the selective hydrogenation reaction of α,β-unsaturated aldehydes (Nature, 2016, Vol. 539, pp. 76-80; Angewandte Chemie International. Edition, 2018, Vol. 57, pp. 5708-5713). Inspired by this, MOF is used as a carrier for the hydrogenation regeneration reaction of NAD(P)H, and the type of MOF is adjusted to achieve the regeneration of NAD(P)H. + The carbonyl groups in the coenzyme NAD(P)H are selectively adsorbed, thereby improving the selectivity of NAD(P)H hydrogenation. However, there is no research report on the use of MOF as a carrier to load metal nanoparticles for the regeneration of coenzyme NAD(P)H hydrogenation. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a highly adjustable MOF-supported metal nanoparticle catalyst and its application in coenzyme NAD(P) + The catalyst preparation method of the present invention is simple, and the composition of the carrier and the metal nanoparticles is adjustable, which solves the problem of the coenzyme (NAD + , NADP + )The problem of low selectivity of 1,4-NAD(P)H hydrogenation regeneration is provided, and a new coenzyme hydrogenation regeneration catalyst is provided.

[0006] On one hand, the present invention relates to a coenzyme hydrogenation regeneration catalyst, wherein the carrier of the catalyst is a Ti-based MOF or an Al-based MOF, and at least one metal nanoparticle is loaded on the carrier, and the metal nanoparticle is at least one of Pt, Pd, Rh, Ir, Ru and / or Ni, and the loading amount of the metal nanoparticle is 0.1-10wt% (preferably 0.3-1.2wt%; particularly preferably 0.8-1.2wt%, within this particularly preferred range, it is helpful to improve the catalytic efficiency of the catalyst); the Ti-based MOF is a metal organic framework material MIL-125-NH2 constructed by titanium ion clusters combined with an organic ligand 2-aminoterephthalic acid, and the Al-based MOF is a metal organic framework material MOF-303 constructed by aluminum ion clusters combined with 3,5-pyrazoledicarboxylic acid.

[0007] In a preferred embodiment of the present invention, the metal nanoparticles are loaded in the pores of the Ti-based MOF.

[0008] In a preferred embodiment of the present invention, the metal nanoparticles are Pt nanoparticles, and the average particle size of the Pt nanoparticles is 1-3 nm. The use of Pt nanoparticles can improve the selectivity of the catalyst.

[0009] Another aspect of the present invention also relates to a method for preparing the above-mentioned coenzyme hydrogenation regeneration catalyst. The preparation method uses a porous MOF material as a carrier, introduces a metal nanoparticle precursor into the porous framework material by an excessive impregnation method, washes the metal salt remaining on the surface of the carrier, and reduces the metal ions in the pores of the framework material into metal nanoparticles in a sodium borohydride solution or in a hydrogen atmosphere under heating conditions, thereby obtaining a MOF-based supported metal catalyst with excellent catalytic performance.

[0010] In a preferred embodiment of the present invention, the following steps can be specifically performed:

[0011] (1) Impregnation: Dissolve the metal nanoparticle precursor (such as chloroplatinic acid, palladium chloride, rhodium chloride, iridium acetylacetonate, ruthenium trichloride, nickel chloride) in an appropriate amount of solvent water, methanol or ethanol, and introduce it to the surface of the MOF material or encapsulate it into the MOF pores by excessive impregnation. The concentration of the metal nanoparticle precursor solution is 1mM-5mM, the mass ratio between the metal ion and the main porous material is 0.1-10:100, the amount of solvent is 0-15ml of solvent per 0.1g of solid material, and the amount of solvent is not 0. The impregnation temperature is room temperature to 50°C, and the impregnation time is 1-48h.

[0012] (2) Washing and drying: Wash with methanol several times to remove the residual precursor ions on the surface of the support, so that most of the metal ions are adsorbed in the pores of the metal organic framework. After drying, a porous material sample loaded with metal precursors is obtained.

[0013] (3) High temperature reduction: The solid material is placed in a 0.1-1.0 mol / L sodium borohydride solution or a high temperature hydrogen atmosphere at 80-300°C for 2-5 hours. The total weight of the catalyst is 100%, and the metal nanoparticle loading is 0.1 wt%-10 wt%.

[0014] The carrier used in the present invention is one of the alkali-stable porous framework materials Ti-based MOF (MIL-125, MIL-125-NH2), Zn-based ZIF (ZIF-8, ZIF-90, MAF-7), Co-based ZIF (ZIF-67), and Al-based MOF-303. The impregnation solvent used is water, methanol, and ethanol. The metal precursor used is chloroplatinic acid, palladium chloride, rhodium chloride, iridium acetylacetonate, ruthenium chloride, nickel chloride or other metal salts.

[0015] Another aspect of the present invention also relates to the use of the above-mentioned coenzyme hydrogenation regeneration catalyst in coenzyme regeneration, preferably, the coenzyme is NAD + , NADP + .

[0016] The preparation method of the present invention has the following advantages:

[0017] 1. The method is simple and effective: the process has few steps, the operation is simple and efficient, and the metal nanoparticle precursor is introduced into the metal organic framework pores by a simple excess impregnation method, and the MOF-based metal nanoparticle catalyst can be obtained by high-temperature hydrogen reduction or sodium borohydride reduction;

[0018] 2. Strong designability: There are many types of MOF materials. Different MOFs can be selected as carriers according to the conditions of catalyst use. The applicability of the catalyst can be further improved by modifying different functional groups on the carrier;

[0019] 3. Strong controllability: By adjusting the metal nanoparticle precursor, different types of metal ions can be introduced into the MOF carrier pores, thereby loading different types of metal nanoparticles; by adjusting the ratio between the amount of metal nanoparticle precursor and the amount of porous material carrier, catalysts with different metal loadings can be prepared;

[0020] 4. Large-scale operation: The MOF carrier synthesis method selected by the method of the present invention is relatively simple and has a high yield. The organic ligand used to synthesize the carrier is relatively cheap, suitable for large-scale industrial production, and has important industrial application prospects.

[0021] The material prepared by the present invention has the following advantages:

[0022] 1. It has a high specific surface area, which is conducive to the transmission and diffusion of substrates such as hydrogen during the catalytic reaction;

[0023] 2. The MOF carrier is highly adjustable to achieve NAD(P) + The carbonyl groups in the ions are selectively adsorbed, thereby improving the selectivity of the 1,4-NAD(P)H product with enzyme activity.

[0024] 3. Has less than coenzyme NAD(P) + The micropore size of the volume can effectively block the coenzyme NAD(P) + Direct contact with metal nanoparticles in the support pores is beneficial to improve the selectivity of 1,4-NAD(P)H;

[0025] 4. It has adjustable surface properties. The surface properties of the catalyst can be regulated by the type of organic ligand functional groups in the carrier; BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The MOF-based metal nanoparticles prepared by the present invention are used for coenzyme NAD (P) + Schematic diagram of highly selective hydrogenation regeneration;

[0027] Figure 2 is the XRD of the Pt / MIL-125-NH2 catalyst prepared in Example 1;

[0028] Figure 3 is the SEM of the Pt / MIL-125-NH2 catalyst prepared in Example 1;

[0029] Figure 4 TEM of the Pt / MIL-125-NH2 catalyst prepared in Example 1;

[0030] Figure 5 is the XRD of the Pt / MOF-303 catalyst prepared in Example 4;

[0031] Figure 6 The NAD catalyzed by Pt / MIL-125-NH2-1wt% prepared in Example 1 + UV-vis spectra of hydrogenation reaction solution before and after enzyme incubation;

[0032] Figure 7 Performance test of different Pt loading amounts of Pt / MIL-125-NH2 catalysts prepared in Examples 1 and 3;

[0033] Figure 8 The Ru / MIL-125-NH2-1wt% catalyzed NAD prepared in Example 2 + UV-vis spectra of hydrogenation reaction solution before and after enzyme incubation;

[0034] Fig. 9Performance test of the Ru / MIL-125-NH2-1wt% catalyst prepared in Example 2; DETAILED DESCRIPTION

[0035] The MOF-based metal nanoparticle catalyst prepared by the present invention is used for coenzyme NAD (P) + Schematic diagram of highly selective hydrogenation regeneration Figure 1 As shown, in order to further illustrate the present invention, the following embodiments are listed, but they do not limit the scope of the invention defined by the appended claims.

[0036] Unless otherwise specified, the reagents involved in the embodiments of the present invention are all commercially available products and can be purchased through commercial channels.

[0037] Example 1

[0038] 200mg MIL-125-NH2 (synthesis method referenced from Journal of the American Chemical Society, 2009, Vol. 131, pp. 10857-10859) was dispersed in 30ml methanol solvent, and a methanol solution containing 4.20mg H2PtCl6 was added dropwise to the MIL-125-NH2 dispersion, stirred at 50°C for 48h, and the metal precursor was introduced into the MOF pores by impregnation. The above sample was collected by centrifugation and washed three times with methanol, dried under vacuum at room temperature, and the dried sample was reduced at 200°C for 2h under H2 atmosphere to obtain a Pt / MIL-125-NH2 catalyst with a metal loading of 1wt%, labeled as Pt / MIL-125-NH2-1.0wt%. XRD results showed that ( Figure 2 ), the catalyst still maintains its original pore structure. SEM results show that ( Figure 3 ), the MOF carrier maintained its original morphology and was not destroyed during the loading and reduction process. TEM results showed that ( Figure 4 ), the size of Pt nanoparticles loaded on the MOF carrier is about 2 nm, and no agglomerated Pt nanoparticles appear on the catalyst surface.

[0039] Example 2

[0040] This embodiment is basically the same as embodiment 1, except that ruthenium chloride is used as the metal precursor and the catalyst is marked as Ru / MIL-125-NH2.

[0041] Example 3

[0042] This embodiment is basically the same as embodiment 1, except that the amount of metal nanoparticle precursor H2PtCl6 added is 2.10 mg, and the catalyst is marked as Pt / MIL-125-NH2-0.5wt%.

[0043] Example 4

[0044] The preparation process of Example 1 was adopted, except that the carrier used was Al-based MOF-303 (the synthesis method is referenced from Science Advances, 2018, Vol. 4, p. eaat3198), and the catalyst was labeled Pt / MOF-303. The XRD results of the Pt / MOF-303 catalyst showed that ( Figure 5 ), the carrier structure is not destroyed after loading metal nanoparticles.

[0045] Example 5

[0046] The performance of the prepared catalysts was evaluated by NAD + The preparation of NADH by hydrogenation is described below. The hydrogenation reaction is carried out in a 300 mL stainless steel reactor. 5 mg of the Pt / MIL-125-NH2-1.0 wt% catalyst prepared in Example 1 and 2 mL of 1.5 mM NAD + The reaction solution (pH=8.0 phosphate buffer) was placed in an ampoule, the reactor was sealed, the air in the reaction system was replaced with H2 6 times, and the reaction was carried out at 37°C and 2MPa H2 for a specific time. After the reaction was completed, the solid catalyst was filtered out, and 0.75mL of the reaction solution was diluted to 15mL with pH=7 phosphate buffer for catalytic performance analysis.

[0047] The diluted 15 mL reaction solution was divided into three equal parts, and the absorption peak intensity of the first dilution at a wavelength of 340 nm was measured by UV-Vis. 19.4 U of alcohol dehydrogenase and 10 μL of propionaldehyde were added to the second dilution in sequence, and incubated in a 37°C water bath for 10 min to specifically convert the 1,4-NADH obtained in the dilution into NAD + The absorption peak intensity at a wavelength of 340 nm was measured by UV-Vis. 2.5 U of glucose dehydrogenase and 2.25 mg of glucose were added to the third dilution, and incubated at 37°C in a water bath for 10 min. The unreacted NAD + It is specifically converted into 1,4-NADH, and the absorption peak intensity at a wavelength of 340nm is measured by UV-Vis. NAD is calculated based on the difference in UV-Vis absorption peak intensity before and after the dilution is incubated with alcohol dehydrogenase and glucose dehydrogenase. + The conversion rate and selectivity of 1,4-NADH. Its performance test is as follows Figure 6 and 7 As shown, when the loading amount is 1 wt%, the conversion rate is close to 100% in 10 min, and the selectivity is above 60%, showing excellent catalytic activity and selectivity.

[0048] Example 6

[0049] The Ru / MIL-125-NH2-1.0wt% prepared in Example 2 was used as a catalyst for NAD + Performance evaluation of NADH preparation by hydrogenation, its performance test is as follows Figure 8 and 9 As shown, when the loading amount is 1wt%, the conversion rate can reach more than 90% in 3.6h, and the selectivity is about 40%, indicating that the type of metal nanoparticles has a significant effect on the catalytic activity and selectivity. At the same time, side comparison shows that the Pt / MIL-125-NH2 system has excellent catalytic activity and selectivity.

[0050] The above describes the preferred embodiments of the present invention, but it is not intended to limit the present invention. Those skilled in the art may make improvements and changes to the embodiments disclosed herein without departing from the scope and spirit of the present invention.

Claims

1. An application of a coenzyme hydrogenation regeneration catalyst in regenerating a coenzyme, wherein the catalyst carrier is a Ti-based MOF or an Al-based MOF, and the carrier is loaded with at least one metal nanoparticle, wherein the metal nanoparticle is at least one of Pt, Pd, Rh, Ir, Ru and / or Ni, and the loading amount of the metal nanoparticle is 0.1-10 wt%; the Ti-based MOF is a metal organic framework material constructed by a titanium ion cluster combined with an organic ligand 2-aminoterephthalic acid, and the Al-based MOF is a metal organic framework material constructed by an aluminum ion cluster combined with 3,5-pyrazoledicarboxylic acid; the coenzyme is oxidized nicotinamide adenine dinucleotide NAD + and its phosphorylated form NADP + .

2. The use according to claim 1, wherein the metal nanoparticles are loaded in the pores of the Ti-based MOF.

3. The use according to claim 1, wherein the metal nanoparticles are Pt nanoparticles, and the average particle size of the Pt nanoparticles is 1-3 nm.

4. The use according to any one of claims 1 to 3, wherein the coenzyme hydrogenation regeneration catalyst is prepared by the following preparation method, wherein the porous MOF material is used as a carrier, a metal nanoparticle precursor is introduced into the porous framework material by an excessive impregnation method, the metal salt remaining on the surface of the carrier is washed, and the metal ion precursor in the pores of the framework material is reduced to metal nanoparticles in a sodium borohydride solution or in a hydrogen atmosphere under heating conditions, thereby obtaining the coenzyme hydrogenation regeneration catalyst.

5. The use according to claim 4, characterized in that The precursor of the metal particles is one or a combination of chloroplatinic acid, palladium chloride, rhodium chloride, iridium acetylacetonate, ruthenium chloride, and nickel chloride.

6. According to the use of claim 4, the metal ion precursor is dissolved in a solvent to form a precursor solution, and the solvent is one or more of water, methanol, and ethanol; the concentration of the precursor solution is 1 mM-5 mM, the amount of solvent is 0-15 ml of solvent per 0.1 g of solid porous material, the immersion time of the metal ion precursor on the MOF is 1-24 h, and the immersion temperature is room temperature to 50 °C.

7. The use according to claim 4, characterized in that The metal ion precursor is reduced into metal nanoparticles in a hydrogen atmosphere under high temperature conditions, the hydrogen reduction temperature is 80-300 °C, and the reduction time is 2-5 h.

8. The use according to claim 4, characterized in that The metal ion precursor is reduced into metal nanoparticles using sodium borohydride, and the concentration of sodium borohydride is 0.10-1.0 mol / L.

Citation Information

Patent Citations

  • Mesoporous Ru-MIL-125-NH2 catalyst prepared from supercutical fluid

    CN110183677A